Risk factors of early mortality in COVID-19 patients in Indonesia: A retrospective cohort study in a provincial referral hospital of Aceh - Ismayana, Vera; Yanti, Budi; Kurniawan, Ferry D.; Zulfikar, Teuku; Yusuf, Nurrahmah (Narra J, 2023)
Some of coronavirus disease 2019 (COVID-19) patients died after being hospitalized and early mortality is a matter of concern during the pandemic; therefore, it is critical to determine which patients are the most vulnerable of having early mortality. The aim of this study was to determine the risk factors for early mortality among hospitalized COVID-19 patients in Indonesia. A retrospective cohort study was conducted on hospitalized COVID-19 patients from July 2020 to September 2021 at Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia. Demographic data, clinical characteristics, laboratory findings, and mortality were collected. Early mortality was defined as a death before seven days of the hospitalization. Multivariate regression analysis was employed to determine the risk factors associated with early mortality. We included the data of 624 COVID-19 patients who died during the study period. More than half of the patients were male and aged over 50 years old. The average hospitalization period was 10 days and most patients had more than two comorbidities. Chronic lung disease was the most common comorbidity (46.0%) followed by respiratory disease (26.8%) and heart disease (14.3%). Multiple comorbidities and elevated D-dimers exceeding 3376.92 ng/mL were associated with early mortality with OR: 7.029; 95%CI: 2.02–24.43 and OR: 1.000085, 95%CI: 1.000028–1.000142, respectively. In conclusion, early mortality in COVID-19 patients was associated with having multiple comorbidities and elevated D-dimer level. Therefore, it is crucial to assess the presence of comorbidities and routine laboratory test while managing COVID-19 patients in order to prevent the early mortality.